Strategi Kepala Madrasah dalam Mengelola Transformasi Pendidikan Digital di MAN 2 Langkat - Fitri Aulia; Ahmad Zaki; Syarifah Hidayani (Invention: Journal Research and Education Studies, 2026)
This study aims to analyze the strategies implemented by the madrasah principal in managing the digital education transformation at MAN 2 Langkat. The research employed a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation involving the madrasah principal, vice principal for curriculum affairs, teachers, and students as research informants.The results indicate that the strategies for managing digital education transformation were implemented in a planned and gradual manner. Digital transformation was directed toward the integration of technology in learning, the transformation of the madrasah community’s mindset, the strengthening of teachers’ digital competencies, and the development of a digital-based educational management system. These strategies were realized through the use of digital learning media and platforms, digitalization of learning administration, implementation of the Madrasah Digital Report (RDM), utilization of online communication applications, and the use of social media as a tool for madrasah branding. The challenges encountered included disparities in digital competence among human resources, limited facilities and infrastructure, internet network constraints, and the readiness of teachers and students. Efforts to address these challenges were carried out through continuous guidance, technology training, optimization of facilities, and digital literacy assistance.